Radio equipment used in mobile services Part 3. Methods of measurement for receivers for A3E or F3E emissions (BSI, 1990)
Communication equipment, Telecommunication systems, Radiocommunication, Mobile communication systems, Mobile radio systems, Receivers, Radio receivers, Radio equipment, Electronic equipment and components, Bandwidths, Audiofrequencies, Angle modulation, Modulation, Amplitude modulation, Radio disturbances, Sensitivity, Noise (spurious signals), Electrical testing, Reception, Electrical measurement, Signal level, Signal distortion, Frequency response, Gain control, Performance testing, Testing conditions, Test equipment, Circuits